Environmental Education and Environmental Literacy of Students in Basic Education in Partido District, Camarines Sur, Philippines - Mariel R Estrella (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the Study: The primary purpose of this study was to determine how the level of curriculum integration of environmental problems and issues   influence the level of knowledge and attitude of respondents. Methodology: The study used the descriptive-quantitative research deisgn. Primary data were gathered through a survey on the 284 SHS students enrolled in STEM track. Median and mode were used to determine the extent of integration in secondary education and the level of knowledge and attitude of the respondents on environmental problems and issues.  Ordinal regression was used to determine the influence of curriculum integration on the level of knowledge and attitude of respondents. Results and Discussion: Results showed that the respondents are well aware that air pollution is their primary local environmental problem. Curriculum Integration of environmental problems was moderate. Both the knowledge and attitude of the respondents on environmental problems were fair. Results of Spearman correlation showed significant positive relationship between Integration of EE and attitude on environmental  problems (r=0.161, p=0.007). There were also significant positive relationship between attitude and knowledge on Restoration of Environment (r=0.181, p=0.007) and highly significant positive relationship between attitude and knowledge on Status of Biodiversity (r=0.288, p=0.001). Ordinal regression showed that the integration of EE had significant influence at 1.69% variation on the attitude towards environmental problems (p-0.002). The test further revealed that integration of EE had no significant influence to the knowledge on restoration on environment and status of biodiversity. Originality/Novelty of the study: This study contributed knowledge on  curriculum integration  (CI) of environmental education in the STEM track of Senior High School. CI was found to be an important educational strategy to influence the attitude of learners. While CI did not influence the knowledge of learners, the influence on attitude is much more important because a positive attitude leads to responsible behaviors towards the environment.